Ethical consumerism - Healey, Justin (Issues in society (Balmain, N.S.W.), 2013)
Australians live in a consumer society. It can be easy to ignore the fact that every purchase we make has an impact - financially, socially and environmentally. Being an ethical shopper means making conscious choices about what we consume, and how if affects our world. Do we choose low-cost, high-convenience and unnecessary consumption over environmental sustainability, corporate responsibility and actual need? Do the products we purchase harm other humans, animals or the environment? Are the people who produce them working in decent conditions? How can consumers influence producers and retail.